Prenatal sonographic diagnosis of congenital ductus arteriosus aneurysm: A case report - Tongprasert F. (2014)
The objective of this report was to demonstrate prenatal sonographic features of congenital ductus arteriosus aneurysm (DAA), a rare, but possibly fatal abnormality. It is characterized by a saccular or fusiform dilatation of the ductus arteriosus. The majority of affected neonates are clinically asymptomatic and tend to progressively diminish in size of DAA and spontaneous closure. However, serious complications can occur during waiting periods, including spontaneous rupture or thromboembolism. Case: A 35 year-old Thai woman, G2P1, underwent ultrasound examination at 34 weeks' gestation. Fetal echocardiography revealed markedly enlarged and tortuous ductus arteriosus with saccular dilation at the distal end, just before joining the descending aorta. The cross-sectional diameter of the saccular portion of the ductus arteriosus was 10 mm. The active female baby was vaginally delivered at 34 weeks' gestation, weighing 1050 grams. Postnatal echocardiography confirmed the prenatal findings. The DAA was gradually decreased in size and finally spontaneously closed without medical or surgical intervention.